2009
DOI: 10.1128/aem.00715-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Central Metabolic Pathways in Thermoanaerobacter sp. Strain X514 via Isotopomer-Assisted Metabolite Analysis

Abstract: Thermoanaerobacter sp. strain X514 has great potential in biotechnology due to its capacity to ferment a range of C 5 and C 6 sugars to ethanol and other metabolites under thermophilic conditions. This study investigated the central metabolism of strain X514 via 13 C-labeled tracer experiments using either glucose or pyruvate as both carbon and energy sources. X514 grew on minimal medium and thus contains complete biosynthesis pathways for all macromolecule building blocks. Based on genome annotation and isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…From their detailed analysis, the authors concluded that a Re-type citrate synthase (Re-CS) (EC 2.3.3.3) was present. Similar studies were recently done for several other strictly anaerobic bacteria (3,5,8,32). Such atypical citrate synthases of the Re type were first observed in the strictly anaerobic firmicute Clostridium kluyveri (11) but were later also found in other strictly anaerobic bacteria (9,10,21).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…From their detailed analysis, the authors concluded that a Re-type citrate synthase (Re-CS) (EC 2.3.3.3) was present. Similar studies were recently done for several other strictly anaerobic bacteria (3,5,8,32). Such atypical citrate synthases of the Re type were first observed in the strictly anaerobic firmicute Clostridium kluyveri (11) but were later also found in other strictly anaerobic bacteria (9,10,21).…”
supporting
confidence: 59%
“…The resulting labeled [ 13 C]citrate was subsequently cleaved to oxaloacetate plus acetate with Si-citrate lyase in the presence of NADH and malate dehydrogenase so that the oxaloacetate formed was converted to malate. Therefore, the expected products formed from Si-citrate synthase were malate plus [2][3][4][5][6][7][8][9][10][11][12][13] C]acetate, whereas in the case of Re-citrate synthase the products were [2][3][4][5][6][7][8][9][10][11][12][13] C]malate plus acetate (21). The stereospecificity of the purified enzyme was corroborated by detecting 13 C-labeled and unlabeled malic acid produced during the citrate cleavage both in the Si-citrate synthase and in the recombinant enzyme assays.…”
mentioning
confidence: 72%
“…Glutamate derived from [1-13 C]acetate was mainly labeled on C-1 (␣-carboxyl group) in Dehalococcoides strains (19,51,52), and this labeling pattern was consistent with that of glutamate in Thermoanaerobacter sp. (16) and Desulfovibrio vulgaris (18). Especially, the pattern of glutamate (C-1 and C-3) in Dehalococcides strains is exactly in accord with the predicted pattern (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, there are an increasing number of anaerobic bacteria containing Re-citrate synthase (16)(17)(18)(19)(20). As shown in Fig.…”
mentioning
confidence: 88%
“…The dynamic isotope labeling approach (kinetic flux profiling) that we use here is different from the steady-state isotopic approach (metabolic flux analysis) recently used in similar contexts (6,29). One major advantage of our approach is that it provides absolute fluxes throughout the network instead of just ratios of fluxes at branch points.…”
Section: Discussionmentioning
confidence: 99%